Healing and Psychotherapy Model through the Emotional-Spiritual Power: A Case Study of Prisoners in Semarang - Hidayat, Taufiq (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
Stress and depression are two common problems experienced by prisoners. These two problems are even able to lead to new problems, such as a fight between prisoners, drug trafficking, sexual abuse, and suicide. A new approach addressing those problems is required, one of which is through the development of emotional and spiritual awareness. Using mix-method and quasi-experimental design, this study focuses on how to increase emotional and spiritual awareness of the prisoners in Semarang who have joined a healing and psychotherapy program named Emotional-Spiritual Power (ESP). Through experimental analysis with Ttes and descriptive analysis, the study found that the ESP program is influential in enhancing the prisoner’s emotional and spiritual awareness significantly. The program helps them transform into a new person with positive energy in the mind, heart, and behavior. This way, all the internal problems that reside within the prisoners, such as stress and depression, can be cured.